Assessment of genetically modified cotton GHB614 × T304‐40 × GHB119 for food and feed uses, import and processing under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2014‐122). (25th July 2018) - ; Naegeli, Hanspeter; Birch, Andrew Nicholas; Casacuberta, Josep; De Schrijver, Adinda; Gralak, Mikołaj Antoni; Guerche, Philippe; Jones, Huw; Manachini, Barbara; Messéan, Antoine; Nielsen, Elsa Ebbesen; Nogué, Fabien; et al.
Abstract: The three‐event stack cotton GHB614 × T304‐40 × GHB119 was produced by conventional crossing to combine three single events, GHB614, T304‐40 and GHB119. The genetically modified organisms (GMO) Panel previously assessed the three single cotton events and did not identify safety concerns. No new data on the single cotton events that could lead to modification of the original conclusions on their safety were identified. Based on the molecular, agronomic, phenotypic and compositional characteristics, the combination of the single cotton events and of the newly expressed proteins in the three‐event stack cotton did not give rise to food and feed safety concern. The GMO Panel considers that the three‐event stack cotton GHB614 × T304‐40 × GHB119 has the same nutritional impact as its comparator and the non‐GM reference varieties tested. The GMO Panel concludes that the three‐event stack cotton GHB614 × T304‐40 × GHB119, as described in this application, is nutritionally equivalent to and as safe as its comparator and the non‐GM reference varieties tested, and no post‐market monitoring of food/feed is considered necessary. In the case of accidental release of viable GHB614 × T304‐40 × GHB119 cottonseeds into the environment, this three‐event stack would not raise environmental safety concerns. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of cotton GHB614 × T304‐40 × GHB119 seeds. The GMO Panel concludes that cotton GHB614 × T304‐40 × GHB119, as described in this application, is as safe as its comparator and the tested non‐GM reference varieties with respect to potential effects on human and animal health and the environment.